Board-level employee representation in Portugal: A process (slow) in the making - Costa, H.; Rego, R. (Revisiting worker representation on boards: The forgotten EU countries in codetermination studies, 2025)
A broad range of concepts can be applied to the theme of board-level employee representation (BLER): ‘labour/industrial/workplace democracy’ (Hyman 2016; Conchon and Waddington 2015; Stoleroff 2016); ‘labour participation’ (Conchon and Waddington 2015); co-management or codetermination; ‘representativeness’ (Costa and Rego 2021); and ‘information and consultation’ (Estanque et al. 2020), among others (see also the introductory chapter in this volume). It is doubtful if any of these concepts can be analysed in isolation and so it is admissible (even desirable) to stimulate a ‘dialogue’ between them as a means of empowering the forms of worker representation in companies.